The relative age effect on anthropometry, body composition, biological maturation and motor performance in young Brazilian soccer players - Altimari, J. M.; Altimari, L. R.; Bortolotti, H.; Ferreira Junior, A.; Gabardo, J. M.; Buzzachera, C. F.; Frisselli, A.; de Moraes, A. C. (Journal of Human Kinetics, 2021)
The present study aimed to investigate the influence of months of birth on anthropometry, body composition, biological maturation, and motor performance in young Brazilian soccer players. Young Brazilian soccer players from the Under-13 (n = 50; 13.6 ± 0.3 years), Under-15 (n = 50; 15.5 ± 0.4 years), and Under-17 categories (n = 46; 17.7 ± 0.3 years) took part in this study. Athletes were divided according to chronological age, 1st tertile (January to April); 2nd tertile (May to August); and 3rd tertile (September to December). Anthropometry, body composition, biological maturation, and motor performance variables were evaluated for all participants. There were no differences between the U-13, U-15, and U-17 categories regarding birth tertiles (p > 0.05). Differences between the ages and birth tertiles were observed for the stature, body mass, and lean body mass (p < 0.05). Moreover, differences were found in maturational status between the ages and birth tertiles (p < 0.05). In general, U-13 players showed lower values compared to U-15 and U-17 players in tests of motor performance. In addition, there was a difference in motor performance between the birth tertiles only for RSA variables. The months of birth influenced the stature, body mass, lean body mass, and repeated sprint ability in the U-13 and U-15 categories. Thus, care should be taken during the process of talent selection, as many young players could be underestimated due to their date of birth.